2019
DOI: 10.1167/iovs.18-26489
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Polymorphisms at theSIX1-SIX6Locus With Primary Open-Angle Glaucoma

Abstract: PURPOSE. To evaluate the association of single-nucleotide polymorphisms (SNPs) in the SIX1-SIX6 locus with primary open-angle glaucoma (POAG) through a systematic review and metaanalysis from 22 studies. METHODS. To our knowledge, all case-control association studies on SNPs in the SIX1-SIX6 locus and POAG reported up to August 30, 2018, in PubMed, Embase, and Web of Science were retrieved. Unadjusted and adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) for each SNP were calculated using a fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…However, in the case of POAG and SIX1/SIX6 , it is not known when these genetic variants start exerting their effects 24 . Studies have reported that individuals with risk allele in SIX1/SIX6 are more susceptible to glaucoma 1 , 3 , 25 and have thinner RNFL 20 23 . Note that these RNFL studies were conducted in older individuals, hence it is not clear whether thinner RNFL found in the older individuals with SIX1/SIX6 variants is due to these individuals being born with thinner RNFLs or due to a faster rate of RNFL degeneration as they age.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of POAG and SIX1/SIX6 , it is not known when these genetic variants start exerting their effects 24 . Studies have reported that individuals with risk allele in SIX1/SIX6 are more susceptible to glaucoma 1 , 3 , 25 and have thinner RNFL 20 23 . Note that these RNFL studies were conducted in older individuals, hence it is not clear whether thinner RNFL found in the older individuals with SIX1/SIX6 variants is due to these individuals being born with thinner RNFLs or due to a faster rate of RNFL degeneration as they age.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mutations in paired box 6 (PAX6) gene are rare with large biological effect and are closely associated with the pathogenesis of developmental glaucoma related to anterior segment dysgenesis [91]. Variants of genes with common frequency and low effect size leading to the development of POAG include the following: Cyclin-dependent kinase inhibitor 2B (CDKN2BAS), caveolin 1 and caveolin 2 (CAV1/CAV2), sine oculis homeobox homolog 1 and sine oculis homeobox homolog 6 (SIX1/SIX6), transmembrane and coiled-coil domains 1 (TMCO1), growth arrest specific 7 (GAS7), atonal homolog 7 (ATOH7), and RPGR Interacting Protein 1 (RPGRIP1) [88,91,[99][100][101][102][103][104][105][106][107].…”
Section: Genes As Risk Factors For Poag Pathogenesismentioning
confidence: 99%
“…During embryonic development, SIX1 is expressed broadly in multiple tissues, including the otic vesicle and the limb mesenchyme. The putative roles of SIX1 with respect to POAG, high tension glaucoma, and NTG are based on association between some SIX1 sequence variations and these phenotypes (S. Y. Lu et al, 2019). Specific associations with IOP were also reported (Y. Chen et al, 2015).…”
Section: Transcription Factorsmentioning
confidence: 99%